PENGARUH PERAN GANDA, STRESS KERJA, DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PEREMPUAN PT. PANTJATUNGGAL KNITTING MILL - Yohana T Simanjuntak; Rodhiyah Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2018)
The research problem is low productivity of employee at department of production at PT. Pantjatunggal Knitting Mill. The purpose of this research is to identify the influence of the dual role of women employee, work stress and discipline work against female employees work productivity in PT. Pantjatunggal Knitting Mill. Type of research is explanatory. The sampling technique used is probability sampling, with proportionate sampling type. Samples were taken with the Slovin formula of 10% (0.10), and obtained a sample of 84 respondents using a questionnaire. The analysis method is with correlation, the coefficient determination, t test, and f test by using SPSS 21.0 for windows. The Results of the categorization show that of most employees have a double role is high enough. Have a significant influence (partial) with low correlation (0,036), coefficient determination 3,6%, t count (-1,747). Categorization work stress categorization of most employees is high and have a significant influence (partial) with low correlation (0,067), coefficient determination 6,7%, t count (-2,004). Discipline of work categorization of most employees have a good discipline have a significant influence (partial) with medium correlation (0,401), coefficient determination 16,1%, t count (3,961). Dual role, work stress, and discipline of work variables together (simultaneously) have a positive and significant effect on work productivity with medium correlation (0,036), coefficient determination 18,3%, and f count (5,964). The conclusions are that the dual role, work stress, and work discipline have a positive and significant effect on work productivity. The suggestions that the management need to pay attention to employees, to provide clear information to employees, and to gave sanction based on the rules.